PENGARUH PROGRAM PEMBERDAYAAN PEREMPUAN TERHADAP KESEJAHTERAAN IBU RUMAH TANGGA DI DESA SEREANG - Mahani Mahani; Muhammad Arisal Asad; Abdul Razak Useng (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
The purpose of this study is to see how the Women's Empowerment Program affects housewives in Sereang Village, Maritengngae District, Sidenreng Rappang Regency. In this study, the population was determined to be 21 persons, and the research sample was a saturated sample, consisting of 21 people. The following data gathering strategies were used in this study: (1) observation, (2) questionnaire, and (3) literature review. Following that, the data was examined using frequency and percentage tables. The results revealed that the Women's Empowerment Program had a 76.3 percent positive impact in Sereang Village, Maritengngae District, Sidenreng Rappang Regency, and that the welfare of housewives in Sereang Village, Maritengngae District, Sidenreng Rappang Regency was 76.6 percent positive, The average percentage value of the indicator is 72.81 percent with a good category based on the results of SPSS data processing, it turns out that the t-count> t-table (3.434> 2.093), then Ho is rejected and Ha is accepted, indicating that each independent variable and the dependent variable have an effect / are significant.